Peripheral Nerves: Not Only Cross-sectional Area in the Era of Radiomics - Tagliafico, Alberto Stefano; González, Raquel Prada; Rossi, Federica; Bignotti, Bianca; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2020)
The peripheral nervous system is increasingly being investigated using medical imaging as a complement or in association with electrodiagnostics tests. The application of imaging techniques, such as ultrasound (US) and magnetic resonance imaging (MRI), allows detailed visualization of the peripheral nervous system. According to the European Society of Musculoskeletal Radiology, the use of US for nerve evaluation is strongly encouraged. In addition, the role of US is further enhanced by the wide application of US-guided techniques to diagnose or to treat peripheral nerve disorders.Standard evaluation of peripheral nerves on US usually relies on cross-sectional area evaluation with different cutoff values in the osteofibrous tunnels and outside them. In several anatomical areas, side-to-side comparison is highly recommended because it helps distinguish subtle variations by using the unaffected limb as an internal control.US is widely used to perform US-guided interventional procedures on peripheral nerves. The recent development of radiomics and machine and deep learning applied to peripheral nerves may reveal new insights beyond the capabilities of the human eye. Radiomics may have a role in expanding the diagnostic capabilities of US and MRI in the study of peripheral nerve pathology, especially when the cross-sectional area is not markedly increased.
Keywords: peripheral nerve; ultrasound; magnetic resonance imaging; radiomics; cross-sectional area